2010
DOI: 10.1016/j.ijheh.2010.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Fishing activity, health characteristics and mercury exposure of Amerindian women living alongside the Beni River (Amazonian Bolivia)

Abstract: Populations in Bolivian Amazonia are exposed to mercury contamination through fish ingestion. A group of 170 Amerindian women living along the banks of the Beni River were examined in order to detect any adverse effects on their health consistent with the toxic effects of mercury. The mercury content of the women's hair (H-Hg) was used as the bio-indicator of mercury exposure. The women answered a 24-hour food recall questionnaire on the frequency of their fish consumption. They also underwent a clinical exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 35 publications
3
22
0
Order By: Relevance
“…It has been also reported that the consumption of 150 g of either louvar or swordfish, acquired from fish retailers in Madrid (Spain), exceeded the recommended value of PTWI for mercury in women in childbearing age, whereas for Cd and Pb it did not [ 53 ]. This is an important issue, considering the human health threats associated with methyl mercury exposure through intake [ 1 , 15 ] affecting public health, mainly in children [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been also reported that the consumption of 150 g of either louvar or swordfish, acquired from fish retailers in Madrid (Spain), exceeded the recommended value of PTWI for mercury in women in childbearing age, whereas for Cd and Pb it did not [ 53 ]. This is an important issue, considering the human health threats associated with methyl mercury exposure through intake [ 1 , 15 ] affecting public health, mainly in children [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Prenatal exposure through consumption of fish with high concentrations of methyl mercury causes serious diseases, such as cerebral palsy, mental retardation, neurological abnormalities and more infant mortality [ 1 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that overall, the data did not provide strong evidence for an association between mercury in blood and lower scores on neurobehavioural performance tests in this population. Benefice et al (2010) examined neurological abnormalities and blood pressure among two ethnic groups of Amerindian women living along the banks of the Beni River (n = 170). Total mercury in hair (mean 5.5, SD 4.2 mg/kg) and frequency of fish consumption was recorded by a 24-h food recall questionnaire.…”
Section: Neurotoxicity In Adultsmentioning
confidence: 99%
“…Thus, evidences between exposure to mercury and an increase in the risk of heart diseases were not observed, although Benefice et al 44 suggest that there may be a relation with higher susceptibility of developing other diseases, such as neurological disorders.…”
Section: Fish Consumption and Fish Contaminantsmentioning
confidence: 99%
“…Benefice et al 44 reported that the increase in blood mercury levels among Amerindians living in the Bolivian Amazon, also related with fish consumption, was associated with a higher susceptibility in developing neurological disorders. .Most of the other studies that explain the risks of fish consumption are limited to identification and quantification of contaminants in varied species.…”
Section: Fish Consumption and Fish Contaminantsmentioning
confidence: 99%